Comparative Theology and Scriptural Reasoning: A Muslim's Approach to Interreligious Learning - Avci, Betül (Religions, 2018)
In this paper, I examine Comparative Theology (CT) and Scriptural Reasoning (SR), two distinctive interreligious learning practices, in relation to each other. I propose that these practices, with respect to their dialogical features and transformative power, represent two of the most noteworthy current modes of interreligious dialogue. They achieve this by their ability to explicitly understand the other. This is also because they serve not only as tools in service of understanding in academic circles, but also as existentially/spiritually transformative journeys in the exotic/familiar land of the other. In respect to religious particularity and (un)translatability, I argue that both CT and SR have certain liberal and postliberal features, as neither of them yields to such standard taxonomies. Finally, I deal with Muslim engagement with CT and SR and present some initial results of my current comparative questioning/learning project. Consequently, I plan for this descriptive work to stand as a preliminary to, first, an SR session that focuses on some Qur'anic verses and biblical accounts with a probable progressivist view of history and, second, an in-depth study of the Islamic tradition in that light.